The majority of sialylated glycoproteins in adult Ixodes ricinus ticks originate in the host, not the tick - Sterba, Jan; Vancova, Marie; Sterbova, Jarmila; Bell-Sakyi, Lesley; Grubhoffer, Libor (Carbohydrate research, 2014)
The presence of sialylated structures in tick organs was observed previously using lectin staining. Recently, we demonstrated the presence of sialylated N-glycans using mass spectrometry in tick salivary glands and the gut. However, we proposed a host (blood) origin for these glycans and mapped the transport of sialylated molecules from the gut to the salivary glands. In this report, we performed quantitation of whole sialic acid and of metabolically incorporated sialic acid (N-azido neuraminic acid) in Ixodes ricinus tick samples. We show that the majority of sialylated molecules in the adult tick originate in the host (blood) and are not synthesized by the tick. Similar results were observed for tick cell cultures. The almost complete absence of tick sialylated molecules and the specific transport and localization of host structures into the tick salivary glands and the saliva raises many questions on the role of these molecules in the physiology and, specifically, the blood-feeding of ticks.
Keywords: Ixodes ricinus; Tick cell line; glykoproteiny; Cell Line; N-Acetylneuraminic Acid; klíště; Host-Parasite Interactions; Saliva; interakce hostitele a parazita; Glycoproteins; Click chemistry; Animals; ženské pohlaví; Sialic acid; zvířata; Ixodes; buněčné linie; sliny; Tick; kyselina N-acetylneuraminová; Female; Thiobarbituric acid assay